2007 IEEE Symposium on VLSI Circuits 2007
DOI: 10.1109/vlsic.2007.4342694
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Variability Optimization Strategies in a Sub-200mV, 3.5pJ/inst, 11nW Subthreshold Processor

Abstract: Matching between PFET and NFET devices, achieved by adjusting A robust, energy efficient subthreshold (sub-Vth) processor has been the body bias differential, maximizes noise margins in the sub-Vth designed and tested in a 0.13ptm technology. The processor con-regime. Fig. 5 shows how the minimum functional Vdd (Vddlimit), a sumes InW at Vdd=I6OmV and 3.5pJ/inst at Vd,r=35OmV. Variabil-strong indicator of noise margins [6], is reduced from 180mV to ity and performance optimization techniques are investigated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 0 publications
0
28
0
Order By: Relevance
“…It has been shown in [5] that the delay variabilities present in sub-threshold circuits have fundamental impact on the design, e.g. shifting the supply voltage at which the minimum energy operation point is expected, which has been also verified by measurements [6].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…It has been shown in [5] that the delay variabilities present in sub-threshold circuits have fundamental impact on the design, e.g. shifting the supply voltage at which the minimum energy operation point is expected, which has been also verified by measurements [6].…”
Section: Introductionmentioning
confidence: 75%
“…Wire resistances are not taken into consideration, because they become negligible compared to the effective transistor output resistances at sub-threshold supply voltages as already pointed regarding the supply lines in [6]. To estimate the worst-case error made by omitting wire resistance, delays for the strongest inverter in the considered library have been determined using the wire resistance/capacitance combinations given for different fanouts in the wireload.…”
Section: B Model Verificationmentioning
confidence: 99%
“…Fig. 3 plots the change in power consumption of low-power LSI chips reported from 2007 to 2014 at ISSCC and VLSI Circuits [3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37], which are the most popular international conferences in the semiconductor industry. It is found that there are three domains: milliwatt, microwatt, and nanowatt.…”
Section: Trends In Circuit Technology and Energy Harvestingmentioning
confidence: 99%
“…These two types of variations are handled in different ways. The inter-die variation can be effectively mitigated by body biasing [14]. Thus, in this work, we account for the intra-die variation only and consider the delays follow the Gaussian distribution , .…”
Section: Timing Variabilitymentioning
confidence: 99%